Innovative solution for overcurrent relay coordination studies in power delivery networks using optimisation techniques - Papaspiliotopoulos, Vasileios A; Korres, George N (Journal of engineering (Stevenage, England), 2018)
This study presents a software package developed to carry out overcurrent (OC) protection coordination studies for power delivery networks, making use of versatile optimisation models and robust solvers. The problem of setting and coordinating OC functions in modern numerical relays is formulated as a minimisation problem, subject to technical constraints which are relevant to the protection practises applied by utilities. The proposed solution aims to assist protection engineers in calculating optimum OC setting values, which is a labour-intensive task.